In-Vitro Effectiveness of Ethanol Extract of Permot Leaf (Passiflora foetida Linn.) Towards Mortality of Rhipicephalus sanguineus Larvae - Intan Nurcahya; Poedji Hastutiek; Ratna Damayanti; Iwan Sahrial Hamid; Agus Wijaya (Universitas Airlangga, 2020)
This study had three fold objective which were finding the effectiveness of ethanol extract of permot leaf (Passiflora foetida Linn.) towards mortality of Rhpicephalus sanguineus (R. sanguineus) larvae in vitro and also identifying lethal concentration and lethal time. Completely randomized design was used with six treatments and four replications. Five R. sanguineus were used in the treatment for all replication. The observation of mortality was done every ten minutes in five hours. Rhpicephalus sanguineus larvae were dead if there was no movement. The collected data was analyzed using ANOVA factorial and followed by Duncan’s test. The obtained data showed that ethanol extract of permot’s leaf ethanol extract was effective toward mortality of R. sanguineus larvae in vitro. The suspension of 10% extract concentration of permot leaf ethanol extract has a similar effectiveness as Noticks®. Probit analysis stated that LC50 can be reached by using the 4% concentration in two hours and 2.4% concentration in five hours. LC95 can be reached by using the 6.5% concentration in two hours and 3.93% concentration in five hours. The quickest LT50 can be reached in 0.91 hours and LT95 2.37 hours after treatment with 10% concentration.